DOI: 10.58530/2022/1945
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes to perivascular and parenchymal fluid flow dynamics with multi-compartment diffusion MRI

Abstract: Perivascular spaces (PVS) play a critical role in fluid transfer and waste clearance in the brain. PVS enlargement is associated with advancing age; however, the functional correlates of these changes are not well understood. Using multi-compartment diffusion models, we assessed the diffusion properties within the PVS and the surrounding parenchyma in a healthy aging cohort. We found age was significantly associated with increased perivascular free water content and reduced parenchymal free water content. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…MRI studies have looked at the relation between MRI‐visible PVS occurrence and characteristics of ISF PAR . Using multi‐compartment diffusion models, a preliminary study 75 found that age was related to both increased perivascular FW content and reduced parenchymal FW content, which might suggest age‐related changes to perivascular fluid transfer.…”
Section: Mri Techniquesmentioning
confidence: 99%
“…MRI studies have looked at the relation between MRI‐visible PVS occurrence and characteristics of ISF PAR . Using multi‐compartment diffusion models, a preliminary study 75 found that age was related to both increased perivascular FW content and reduced parenchymal FW content, which might suggest age‐related changes to perivascular fluid transfer.…”
Section: Mri Techniquesmentioning
confidence: 99%